2011
DOI: 10.1177/1740774511423947
|View full text |Cite
|
Sign up to set email alerts
|

Designing a smoking cessation intervention for the unique needs of homeless persons: a community-based randomized clinical trial

Abstract: Background Although smoking prevalence remains strikingly high in homeless populations (~70% and three times the US national average), smoking cessation studies usually exclude homeless persons. Novel evidence-based interventions are needed for this high-risk subpopulation of smokers. Purpose To describe the aims and design of a first-ever smoking cessation clinical trial in the homeless population. The study was a two-group randomized community-based trial that enrolled participants (n = 430) residing acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Study design and recruitment procedures have been described in detail in a separate manuscript ( Goldade et al, 2011 ). Figure 1 shows an overview of study procedures.…”
Section: Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study design and recruitment procedures have been described in detail in a separate manuscript ( Goldade et al, 2011 ). Figure 1 shows an overview of study procedures.…”
Section: Design Setting and Participantsmentioning
confidence: 99%
“…Intervention components of the study have been described in detail elsewhere ( Goldade et al, 2011 ) but summarized briefl y below.…”
Section: Intervention Componentsmentioning
confidence: 99%
“…In a study following 754 chronically homeless adults, despite 48% of the smokers reporting they were trying to limit their smoking and 75% reporting they had discussed smoking cessation with a health care professional, there were no significant reductions in smoking status at the one year follow up 2 . There are few studies evaluating smoking cessation among homeless smokers, as they are often excluded from smoking cessation clinical trials 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that for both men and women, individuals who smoked heavily were more likely to have higher frailty scores 49 . Among homeless adults, smoking is a considerable challenge 50 ; in fact, one study found that nearly 80% of chronically homeless adults (n=754) were current cigarette smokers 51 .…”
Section: Behavioral Factorsmentioning
confidence: 99%